Profit Growth in Indonesian Sharia Bank: the Impact of RGEC - Akhyar, Chairil; ., Marzuki; ., Azhar; Syamni, Ghazali (International Journal of Engineering and Technology, 2018)
The purpose of this study aims to examine the impact of RGEC implementation on the growth of Sharia Banking profit in Indonesia. This study uses data of financial statements of 11 Sharia banking Indonesia during the year 2012-2014. This research uses panel regression model in testing RGEC factor on profit growth. Based on the data indicates that Sharia banking is still at risk, but GCG, ROA and CAR are still in a maintained position. Statistically this study found that NPF, CAR, inflation and Sharia banking activities affect the profitability of these banks. This indicates that Sharia banking has experienced risk and profitability problems. Economic problems inevitably affect Indonesian banks as it is seen that the level of profitability and inflation are not much different from each other.Â Â